Cybersecurity for dummies - Steinberg, Joseph (Tantor Media, Inc., 2019)
If keeping your business or your family safe from cybersecurity threats is on your to-do list, Cybersecurity For Dummies will introduce you to the basics of becoming cyber-secure! You'll learn what threats exist, and how to identify, protect against, detect, and respond to these threats, as well as how to recover if you have been breached! - The who and why of cybersecurity threats - Basic cybersecurity concepts - What to do to be cyber-secure - Cybersecurity careers - What to think about to stay cybersecure in the future Now is the time to identify vulnerabilities that may make you a victim of cyber-crime-and to defend yourself before it is too late.
Electronic audio file
Keywords: Computer security; Computer networks -- Security measures; Computers; Electronic digital computers; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Ordinateurs; computers; Computer networks; Security measures; Electronic audio books; Downloadable audio books; Audiobooks; Livres audio